Quantum Curvature: Toward the Unity of Relativity and Quantum Mechanics - Xinzhong, Wu (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2017)
Quantum curvature interpretation has greatly promoted the unification of relativity and quantum mechanics in physics thought level. In this paper, we discuss the deep unification of relativity and quantum mechanics according to new research by some scholars. This paper involves the derivition of quantum hypothesis from the relativistic transformation, the relation between Compton's matter wave and De Broglie's matter wave, and the quantum divition mechanism of inertial systems in the superposition principle of quantum states.